Mutational analysis of CLC-5, cofilin and CLC-4 in patients with Dent's disease. - Wu, F; Reed, A; Williams, SE; Loh, N; Lippiat, J; Christie, P; Large, O; Bettinelli, A; Dillon, M; Goldraich, N; Hoppe, B; Lhotta, K; et al. (2009)
BACKGROUND/AIMS: Dent's disease is caused by mutations in the chloride/proton antiporter, CLC-5, or oculo-cerebro-renal-syndrome-of-Lowe (OCRL1) genes. METHODS: Eighteen probands with Dent's disease were investigated for mutations in CLC-5 and two of its interacting proteins, CLC-4 and cofilin. Wild-type and mutant CLC-5s were assessed in kidney cells. Urinary calcium excretion following an oral calcium challenge was studied in one family. RESULTS: Seven different CLC-5 mutations consisting of two nonsense mutations (Arg347Stop and Arg718Stop), two missense mutations (Ser244Leu and Arg516Trp), one intron 3 donor splice site mutation, one deletion-insertion (nt930delTCinsA) and an in-frame deletion (523delVal) were identified in 8 patients. In the remaining 10 patients, DNA sequence abnormalities were not detected in the coding regions of CLC-4 or cofilin, and were independently excluded for OCRL1. Patients with CLC-5 mutations were phenotypically similar to those without. The donor splice site CLC-5 mutation resulted in exon 3 skipping. Electrophysiology demonstrated that the 523delVal CLC-5 mutation abolished CLC-5-mediated chloride conductance. Sixty percent of women with the CLC-5 deletion-insertion had nephrolithiasis, although calcium excretion before and after oral calcium challenge was similar to that in unaffected females. CONCLUSIONS: Three novel CLC-5 mutations were identified, and mutations in OCRL1, CLC-4 and cofilin excluded in causing Dent's disease in this patient cohort.